2014
DOI: 10.5539/jas.v6n3p12
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Extender Viscosity Improves the Quality of Cooled Boar Semen

Abstract: The use of several types of gelling extenders for the storage of semen from several domestic species in the solid state has been shown to have beneficial effects on some semen quality parameters. The objective of this study was to evaluate the effect of a new high-viscosity semen extender, Zoosperm ND-5 3D ® (Import-Vet, Centelles, Spain), on the the quality of boar spermatozoa at preserved at 17ºC for 7 days. Sodium alginate was used for the first time to increase the viscosity of the extender for the liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Several investigations have stated that sperm-cell dilution in a viscous medium prevents cellular sedimentation and favours a reduction in sperm metabolic demand (Nagy et al, 2002;López-Gatius et al, 2005;Corcini et al, 2011). Furthermore, studies on boar sperm have shown that increased viscosity of the medium enhances sperm membrane stability and their ability to move (Coy et al, 2009;Gil et al, 2014;González-Abreu et al, 2017) With regard to the oscillatory shear flow tests, we observed that the viscoelastic properties of semen samples were affected by the freezing-thawing process. This is related to the diminished interactions among the components of the freezing medium and sperm with a damaged plasma membrane (Barnes, 2000;Medina-Torres et al, 2000).…”
Section: Discussionmentioning
confidence: 69%
“…Several investigations have stated that sperm-cell dilution in a viscous medium prevents cellular sedimentation and favours a reduction in sperm metabolic demand (Nagy et al, 2002;López-Gatius et al, 2005;Corcini et al, 2011). Furthermore, studies on boar sperm have shown that increased viscosity of the medium enhances sperm membrane stability and their ability to move (Coy et al, 2009;Gil et al, 2014;González-Abreu et al, 2017) With regard to the oscillatory shear flow tests, we observed that the viscoelastic properties of semen samples were affected by the freezing-thawing process. This is related to the diminished interactions among the components of the freezing medium and sperm with a damaged plasma membrane (Barnes, 2000;Medina-Torres et al, 2000).…”
Section: Discussionmentioning
confidence: 69%